(untitled) (INNOVATIVE ECONOMY, 2019)
Zheliuk T.L. FINANCIAL MARKET DEVELOPMENT IN THE CONTEXT OF NATIONAL SECURITY Purpose. The aim of the article is outlining the determinants of enhancing the competitive potential of the financial services market from the point of view of economic security, adherence to which ensures the balanced development of all institutional sectors, defines opportunities for expanded reproduction. Methodology of research. Systematic, synergistic, institutional approaches and modern methods of analysis are used in the course of the research, in particular the following: a systematic approach for substantiating scientific and methodological evaluation of financial market development; method of complex analysis – to evaluate the effectiveness of financial market development; abstract and logical – for generalizations and conclusions. Findings. The problems of development and management of the financial sector of the national economy from the standpoint of declared vectors of sustainable development are considered. The factors of convergence of the national financial sector with the world financial system, support of own financial stability and security are distinguished. The necessity of active introduction of start-ups into the domestic financial market is substantiated. Originality. The determinants of the development and modernization of the financial services market have been proposed in view of the need to preserve national interests and take into account the current challenges of digitalization. The emphasis is placed on improving the efficiency of regulation of the financial services market and the need to introduce new start-ups into the practice of calculations in the financial services market. Practical value. The proposals received can be used to improve the current system of financial risk management, to regulate and control the quality of financial services and the security of financial payments, to innovate in the financial services market. Key words: financial services market; determinants of sustainable development of the financial sector; financial stability; regulators; the Fin-Tech industry; block-chain technology.